Association of gut‐specific non‐inflammatory T lymphocytes with chronic anorexia nervosa and constitutional thinness. (25th June 2022) - Gabriel, Tristan; Massoubre, Catherine; Hanachi, Mouna; Doré, Joel; Lambert, Claude; Germain, Natacha; Galusca, Bogdan; Paul, Stephane
Abstract: Objective: Previous studies of AN showed low‐grade inflammation. Are low‐grade inflammation and circulating lymphocytes associated with chronic conditions? Method: Peripheric blood cytokines were measured using Luminex™ technology in a chronic AN cohort (mean = 67.42 months), compared to Constitutional Thinness (CT), Constitutional Obesity (CO), and Healthy Controls (HC). Secondarily a prospective cohort of chronic AN (mean = 54.11 months) was recruited to compare the functional lymphocyte profile in blood by flow cytometry to CT and HC. Results: In the AN group, most cytokine concentrations were lower than in CT and HC groups. The IL‐23 (98.02 pg/ml) was elevated related to HC and CO, and the IL‐10 (4.178 pg/ml) was elevated versus CO. In the CT group, IL‐9 (0.06216 pg/ml) was elevated compared to AN. The AN group had high Treg (9.259% of CD4 + ) and CD8 + Integrinβ7 + (9.552% of CD3 + ) versus HC for lymphocyte populations. In CT group, elevated Treg (9.7% of CD4 + ) elevated percentage of CD4 + CCR9 + (5.867% of CD3 + ) and CD8 + Integrinβ7 + (10.21% of CD3 + ) were found versus HC. Conclusions: The chronic state of AN and CT is surprisingly non‐inflammatory with elevated Treg cells. These results suggest that maintaining a dysregulated response to intestinal antigens may contribute to maintaining AN. Key points: Constitutional thinness and chronic anorexia nervosa show that thinness is associated with a close immunological pattern Cytokine profile of constitutional thinness and chronic anorexia nervosa is not pro‐inflammatory Circulating lymphocytes profile in constitutional thinness and anorexia nervosa is not pro‐inflammatory